2022
DOI: 10.3390/pharmaceutics14030549
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Haloperidol in Critically Ill Patients: Is There an Association with Inflammation?

Abstract: Haloperidol is considered the first-line treatment for delirium in critically ill patients. However, clinical evidence of efficacy is lacking and no pharmacokinetic studies have been performed in intensive care unit (ICU) patients. The aim of this study was to establish a pharmacokinetic model to describe the PK in this population to improve insight into dosing. One hundred and thirty-nine samples from 22 patients were collected in a single-center study in adults with ICU delirium who were treated with low-dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…The impact of C-reactive protein (CRP) on exposure to haloperidol following the administration of low haloperidol doses in critically ill adults was described in contribution (16). By constructing its parametric Bayesian model and by performing Monte Carlo simulations, the authors showed that the clearance of haloperidol is negatively correlated with increasing CRP up to approximately 50 mg/L, pointing to the utility of individualized dosing at the intensive care unit to overcome delirium.…”
Section: Miscellaneous Drugsmentioning
confidence: 99%
“…The impact of C-reactive protein (CRP) on exposure to haloperidol following the administration of low haloperidol doses in critically ill adults was described in contribution (16). By constructing its parametric Bayesian model and by performing Monte Carlo simulations, the authors showed that the clearance of haloperidol is negatively correlated with increasing CRP up to approximately 50 mg/L, pointing to the utility of individualized dosing at the intensive care unit to overcome delirium.…”
Section: Miscellaneous Drugsmentioning
confidence: 99%